Kunst en Religie : aspecten van de religieuze beleving in de Vlaamse Kunst 1900-1975. (Hasselt : Provinciebestuur Limburg, 1975)
Baerten, Ben ; Bonduel, Roger ; Burssens, Jan ; Claerhout, Jef ; Colbrandt, Oscar ; De Boeck, Felix ; De Bruycker, Jules ; De Gheus, Luc ; De Grave, J.-Jacques ; De Lannoy, Rene ; De Saegher, Romain ; De Troyer, Prosper ; Devos, Berenice ; De Vriendt, Sam ; English, Joe ; Ensor, James ; Gentils, Vic ; Guiette, Rene ; Hendrickx, Jos ; Joosten, Paul ; Lecossois, Victor ; Broeder Max ; Minnaert, Frans ; Minne, George ; Notebaert, Marcel ; Ost, Alfred ; Permeke, Constant ; Servaes, Albert ; Seuphor, Michel ; Theunynck, Gaston ; Smits, Jacob ; Timmermans, Felix ; Vaerten, Jan ; Van Den Meersch, Vincent ; Van Der Giessen, Arie ; Van De Woestijne, Gustave ; Van Giel, Frans ; Van Hecke, Willem ; Van Offel, Edmond ; Van Overstraete, War ; Van Severen, Dan ; Van Straten, Henri ; Verjans, Raf ; Verstraete, Luc ; Wolfs, Hubert
boek
Keywords: Vlaanderen